Peran Crowdfunding Sebagai Inklusi Keuangan di Era Digital terhadap Pelaku Usaha - Aulia Dila Agustina; Yadila Fany Asrofi; Aan Saputra; Sentot Imam Wahjono (Universitas Kristen Indonesia Toraja, 2026)
Crowdfunding is a method of collective fundraising through a digital platform involving a large number of individuals to support a project, business, or social activity. Over time, crowdfunding has become a technology-based financial innovation (fintech) that provides alternative funding outside of traditional financial institutions such as banks. This study aims to understand the concept of crowdfunding, its types, and its role in supporting the growth of the creative economy and micro, small, and medium enterprises (MSMEs). The method used is a literature study by examining various relevant scientific sources. The results of the study indicate that crowdfunding is divided into several models: donation-based, reward-based, lending-based, and equity-based crowdfunding. Each model has different characteristics and objectives according to funding needs. Crowdfunding has been proven to increase access to capital for entrepreneurs experiencing limitations in conventional financing, while strengthening community participation in digital economic activities. Furthermore, crowdfunding also plays a role in building social engagement, expanding market networks, and increasing transparency in fund management. However, several challenges remain, such as the risk of fraud, a lack of strict regulations, and low digital literacy among the public. Therefore, strengthening regulations and educating the public is necessary to ensure optimal and sustainable development of crowdfunding in Indonesia as a vital instrument in the modern digital economic ecosystem.